The Use of Recycled Objects as English Teaching Media for Young Learners (A Theoretical Review) - Dewantari, Fiorentina (STKIP AGAMA HINDU SINGARAJA, 2021)
This study is a library study about the use of recycled object as teaching media. The use of teaching media is one of the supporting components in teaching. Especially for young learners, the choice of media is an important thing to support them in learning English. Several media can be selected by teachers to be given to young learners. One of them is disposable media in the form of recycled objects that use objects around us. The teacher must be able to create the media to make the learning process more fun and informative. Through recycled objects as teaching media, young learners can learn how to use objects around them without having to use expensive media for learning. Therefore, this article was aimed at sharing the use of recycled objects as English teaching media for young learners. So that, young learners are expected to be motivated in the learning process.